Vitamin B1 delays postharvest senescence and enhances antioxidant accumulation by activating NADPH oxidase in Ziziphus jujuba fruit. (1st August 2022) - Deng, Benliang; Chen, Lijing; Tian, Shan; Shi, Haojie; Zhao, Xusheng
Abstract: Thiamine, also known as vitamin B1 (VB1 ), plays a key role in regulating plant growth and development. However, no studies have addressed its role in regulating postharvest fruit and vegetable senescence. Herein, the effects of VB1 on postharvest senescence and antioxidant-compound accumulation in jujube ( Ziziphus jujuba ) fruit stored at 25 °C were investigated. Soaking postharvest jujube fruit with 1 mmol/L VB1 drastically decreased its weight loss, decay incidence, and respiration rate and improved firmness during the first seven days of storage. VB1 treatment increased jujube fruit NADPH oxidase, superoxide dismutase, and catalase activities, and changed its H2 O2 content. Furthermore, VB1 treatment also dramatically increased the ascorbic acid level, total phenolics content, total flavonoids accumulation, and total antioxidant capacity of the postharvest jujube fruit. However, the increase in antioxidant enzyme activities and antioxidant-compound accumulation were partially reversed by 0.1 mmol/L diphenyleneiodonium chloride, a specific inhibitor of NADPH oxidase. Accordingly, the role of VB1 in delayed fruit senescence and enhanced antioxidant-compound accumulation were discussed in terms of NADPH-oxidase-regulated H2 O2 signaling. Overall, this study provides practical and theoretical information regarding a simple new method for the maintenance of jujube fruit quality during storage at ambient temperature. Graphical abstract: Image 1 Highlights: Thiamine treatment delays postharvest jujube fruit senescence under ambient conditions. Thiamine treatment increases NADPH oxidase, superoxide dismutase, and catalase activities. Thiamine treatment increases ascorbic acid, phenolics, and flavonoids contents. A new method for delaying postharvest jujube fruit senescence is established.